An asymptomatic anterior vaginal wall endometrioma, a rare manifestation of endometriosis: A case report - Elizabeth A. Dilday; Michael S. Lewis; Kiarash Vahidi; Sanaz Memarzadeh (Elsevier, 2020)
A 23-year-old patient with an asymptomatic anterior vaginal wall cyst was referred to gynecology for evaluation and treatment. Preoperative assessment with physical examination and magnetic resonance (MR) imaging of the pelvis was most consistent with Gartner's cyst. Following resection of the cyst wall, histologic evaluation demonstrated endometrial glands, hemosiderin-laden macrophages and inflammation, consistent with vaginal wall endometrioma. This case highlights challenges in the diagnosis of endometriosis in the vagina and in other rare locations, possible mechanisms of development, and proposed treatments.